Analysis by Finite Element Method to Redesign a Jointed-Telescopic Crane for Elevation of Personnel - Diosdado-De la Peña, J.A.; Balvantín, A.J.; Limón-Leyva, P.A.; Pérez-Olivas, P.A. (Проблемы прочности, 2017)
This paper proposes a numerical assessment of a crane for elevation of personnel by finite element analysis, validated with experimental data from constituent components of the crane. The original design of the crane consists of a jointed section of coplanar arms and a telescopic section of collinear arms. As a reference, the standard ANSI/SIA 92.2 was used to determine maximum loads and the consequent effects on the constituent components of the crane. This standard is suitable for crane designs distributed and commercialized in Mexico. The proposed numerical analysis is carried out through a finite element analysis, which is based on the assembly method of kinematic pairs, taking into account dynamic loads and their resulting reaction at each element. The mechanical performance of each component is assessed with the minimal security factor parameter. However, in those components where the MSF was insufficiently in accordance with the standard, a variety of modifications to redesign a given component was proposed. Subsequently, a detailed structural analysis on the proposed redesign was carried out, in which higher security factors were obtained in comparison to the original design. Finally, the numerical results of the proposed redesign were validated through experimental measurements of strain, using strain gauges attached on a crane prototype, which was manufactured according to the proposed redesigned model. Наведено чисельний розрахунок підйомного крана для підняття персоналу на основі скінченноелементного аналізу, підтверджений експериментальними даними по складових його компонентах. Оригінальна модель підйомного крана включає зчленовані секції компланарних стріл і телескопічної секції колінеарних стріл. Максимальні навантаження та іх вплив на складові компоненти підйомного крана визначено згідно зі стандартом ANSI/SIA 92.9, що використовується для моделей підйомного крана, розповсюджених і комерціалізованих у Мексиці. Скінченноелементний аналіз базується на методі складання кінематичних пар з урахуванням динамічного навантаження та їх результуючої реакції на кожен елемент. Механічні характеристики кожного компонента оцінюються за параметром мінімального фактора безпеки. Однак у тих компонентах, де цей фактор не відповідає стандарту, пропонується безліч модифікацій для перепроектування даного компонента. Проведено детальний структурний аналіз запропонованої їх модернізації й отримано більш високі фактори безпеки порівняно з оригінальною моделлю. Чисельні результати запропонованої модернізації підтверджено експериментальними вимірюваннями деформацій при використанні тензодатчиків, установлених на прототипі підйомного крана, який виготовлено згідно із запропонованою перепроектованою моделлю. Представлен численный расчет подъемного крана для поднятия персонала на основе конечноэлементного анализа, подтвержденный экспериментальными данными по составным его компонентам. Оригинальная модель подъемного крана состоит из сочлененных секций компланарных стрел и телескопической секции коллинеарных стрел. Максимальные нагрузки и их влияние на составные компоненты подъемного крана определены согласно стандарту ANSI/SIA 92.2, применяемому для моделей подъемного крана, распространенных и коммерциализированных в Мексике. Конечноэлементный анализ основан на методе сборки кинематических пар с учетом динамических нагрузок и их результирующей реакции на каждый элемент. Механические характеристики каждого компонента оценены по параметру минимального фактора безопасности. Однако в тех компонентах, где этот фактор не соответствует стандарту, предложено множество модификаций для перепроектирования данного компонента. Выполнен также подробный структурный анализ предложенной их модернизации и получены более высокие факторы безопасности по сравнению с оригинальной моделью. Численные результаты предложенной модернизации подтверждены экспериментальными измерениями деформаций при использовании тензодатчиков, установленных на прототипе подъемного крана, который был изготовлен согласно предложенной перепроектированной модели.